Concerned Whether You’ll Make It in Life? Status Anxiety Uniquely Explains Job Satisfaction - Keshabyan, Anna; Day, Martin V. (Frontiers in Psychology, 2020)
Ever feel concerned that you may not achieve your career goals, or feel worried about where your life is going? Such examples may reflect the experience of status anxiety, that is, concerns that one may be stuck or not able to move up in life, or worries that one may be too low in standing compared to society’s standards. Status anxiety is believed to be exacerbated by economic inequality and negatively affect well-being. While job satisfaction is an important determinant of well-being, no research has examined whether status anxiety can also help explain people’s satisfaction with their jobs. We tested whether status anxiety differs from other organizational constructs and uniquely relates to job satisfaction among full-time working adults. In a pilot study we found that status anxiety is separate from the concept of job insecurity (e.g.,, perceived threat of job loss). Results of our main study also indicated that higher status anxiety significantly predicted lower job satisfaction beyond several other indicators of organizational attitudes (job insecurity, occupational self-efficacy, distributive, procedural, and interactional justice), as well as the tendency to seek status and several background factors (e.g., income, education, perceived socioeconomic status). We discuss the unique role of status anxiety in job satisfaction and the implications of this research to our understanding of status concerns as well as organizational attitudes and policies.